Co-Cultures of Mycorrhizal Fungi Do Not Increase Germination and Seedling Development in the Epiphytic Orchid Dendrobium nobile - Shao, Shi-Cheng; Luo, Yan; Jacquemyn, Hans (Frontiers in Plant Science, 2020)
Orchids are highly dependent on mycorrhizal fungi for seed germination and subsequent growth to a seedling as they provide essential carbon, water, and mineral nutrients to developing seeds. Although it is widely known that orchid seeds are often colonized by multiple fungi simultaneously, most in vitro germination experiments focus on mycorrhizal monocultures and little is known about how mycorrhizal assemblages affect seed germination and growth of seedlings. In this study, we compared the effects of mycorrhizal mono- and co-cultures on seed germination and seedling growth of the epiphytic orchid Dendrobium nobile. In situ baiting was used to isolate mycorrhizal fungi from protocorms for germination experiments. Germination experiments were conducted under two light regimes for 90 days. In total, five fungal strains were isolated from protocorms of D. nobile, indicating that the species was not highly specific to its fungal partners. Four strains (JC-01, JC-02, JC-04 and JC-05) belonged to the Serendipitaceae and one (JC-03) to the Tulasnellaceae. Germination percentages were higher under light-dark conditions than under complete dark conditions, supporting previous findings that light facilitates germination in epiphytic orchids. Only two strains were able to induce protocorm formation and growth into the seedling stage. Co-cultures did not result in significantly higher seed germination percentages and seedling development than monocultures. Taken together, these results demonstrate that effects of fungal assemblages are not predictable from those of component species, and that more work is needed to better understand the role of fungal assemblages determining seed germination and subsequent growth under natural conditions.